Yahoo Web Search

  1. Sort by

  1. LHS = xy + xy' = x(y + y') ..........distributive law = x(1) = x RHS = (x+y)(x+y' ) = x+(yy') ...........distributive law = x+(0) .............complement law = x LHS = RHS

    1 Answers · Science & Mathematics · 03/08/2019

  2. ....N. (oxidation number) of H on the LHS = O.N. of H on the RHS = +1...⁻ O.N. of H on the LHS = O.N. of H on the RHS, as...

    3 Answers · Science & Mathematics · 16/02/2019

  3. It is the distributive law, but you have to *prove* that by showing the LHS is a subset of the RHS and the RHS is a subset of the LHS and therefore LHS = RHS. Check the link below.

    1 Answers · Science & Mathematics · 06/02/2019

  4. ... the given P(t) and showing that it equals the LHS. Or you can find the solution by solving the DE this way: ...

    1 Answers · Science & Mathematics · 14/02/2019

  5. ...75707>pi-x>2.52611 {the principal values} Check: take x=0.609 LHS=ln[4-2(0.32723837...)]=1.20762311.. RHS=ln[3+0.32723837...]=1.20214264.. =>LHS...

    3 Answers · Science & Mathematics · 11/02/2019

  6. ... by 5^2 each side to get 5^(b-1)*5^2 = 2 * 5^2. Simplify LHS to get 5^(b-1 + 2) = 2 * 5^2 5^(b+1) = 2 * 5^2 U can compute the ...

    3 Answers · Science & Mathematics · 11/12/2018

  7. ... / R GmM / R = 2*KE and you should recognize the LHS as being equal to -GPE. If you find this helpful, please award...

    1 Answers · Science & Mathematics · 07/05/2019

  8. ...x = c/d Then x = (c/d) - (a/b) RHS is clearly rational while LHS is irrational. This is a contradiction. Hence the sum must...

    4 Answers · Science & Mathematics · 03/08/2019

  1. Try asking your question on Yahoo Answers